Juridical Analysis of Criminal Sanctions Against Perpetrators of Abortion Crimes Reviewed from the Criminal Code and Health Law (Study of Decision Number 333/Pid.Sus/2021/PN Bks) - Minetha, Adelli Ritza; Guntara, Deny; Abas, Muhamad (Dinasti Research, 2025)
Most people consider illegal abortion to be very heinous, uncivilized, depriving potential human beings of their right to life, but on the other hand, an inner struggle occurs between a pregnant person to continue her pregnancy or not. The topic raised in this study is related to a pregnant woman, who may not want her pregnancy to then have an illegal abortion, to understand the criminal punishment given to the perpetrators of the crime of illegal abortion in accordance with the Decision of the Bekasi State Court Number 333/Pid.Sus/2021 PN Bks, as well as to understand the legal regulatory steps taken and decided on the perpetrators of the crime of abortion in Bekasi. The research that the author raises can be obtained with a normative research system by reading the leteration, studying and understanding the more complex Indonesian legal systematics at the core of the problem. To support this research material, the author also analyzes and harmonizes based on theories from study experts that are relevant to the problem with a qualitative approach method. The results of the author's research show that the decision taken by the Bekasi District Court Decision Case Number 333/Pid.Sus/2021/PN Bks, namely the determination of the judge to consider sanctions for the perpetrators of the crime of abortion. Also as a sanction of legal consequences due to illegal abortion, the defendant is legally and convincingly declared guilty and must be held responsible for acts that violate criminal law.